Comparison of Pre and Postoperative Hearing Results after Cartilage Augmentation Type III Tympanoplasty - Shrestha, BL; Bhattarai, H; Bhusai, CL (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Keywords: Air bone gap; chronic media (squamous); canal wall down mastoidectomy; cartilage augmentation type III tympanoplasty DOI: 10.3126/njenthns.v1i2.4752 Nepalese J ENT Head Neck Surg Vol.1 No.2 (2010) p.3-5